Development and Implementation of a School-Wide Institute for Excellence in Education to Enable Educational Scholarship by Medical School Faculty. Issue 1 (2nd January 2018) - Cofrancesco, Joseph; Barone, Michael A.; Serwint, Janet R.; Goldstein, Mitchell; Westman, Michael; Lipsett, Pamela A.
ABSTRACT: Problem : Educational scholarship is an important component for faculty at Academic Medical Centers, especially those with single-track promotion systems. Yet, faculty may lack the skills and mentorship needed to successfully complete projects. In addition, many educators feel undervalued.Intervention : To reinvigorate our school's educational mission, the Institute for Excellence in Education (IEE) was created. Here we focus on one of the IEE's strategic goals, that of inspiring and supporting educational research, scholarship, and innovation.Context : Using the 6-step curriculum development process as a framework, we describe the development and outcomes of IEE programs aimed at enabling educational scholarship at the Johns Hopkins University School of Medicine.Outcome : Four significant programs that focused on educational scholarship were developed and implemented: (a) an annual conference, (b) a Faculty Education Scholars' Program, (c) "Shark Tank" small-grant program, and (d) Residency Redesign Challenge grants. A diverse group of primarily junior faculty engaged in these programs with strong mentorship, successfully completing and disseminating projects. Faculty members have been able to clarify their personal goals and develop a greater sense of self-efficacy for their desired paths in teaching and educational research.Lessons Learned : Faculty require programs and resources for educational scholarship and career development, focused on skills building in methodology, assessment, and statistical analysis. Mentoring and the time to work on projects are critical. Key to the IEE's success in maintaining and building programs has been ongoing needs assessment of faculty and learners and a strong partnership with our school's fund-raising staff. The IEE will next try to expand opportunities by adding additional mentoring capacity and further devilment of our small-grants programs.